Optimization of LPG Distribution Route Using Variable Neighborhood Tabu Search Algorithm - Jasmine Athifa Azzahra; Budi Santosa (Jurnal Teknik ITS, 2021)
PT. Galaxi Energi Pratama (GEP) is one of the biggest distributors of subsidized LPG in Malang Raya area. Currently the route planning is not done very well, which results in a high fuel cost. With the company's main business process being distribution, the planning needs to be improved to maximize the profit. The problem in PT. GEP is classified as the Heterogeneous Vehicle Routing Problem with Multiple Trips (HVRPM). This problem is classified as NP-Hard and requires high computational effort to obtain a good solution so metaheuristic method is preferred. In this research, variable neighborhood tabu search (VNTS) algorithm is developed to solve the HVRPM and implemented to minimize the fuel cost of PT. GEP. The developed algorithm is implemented in the six instances collected from the case study. The generated trips produce a total savings of Rp 150,876 for one operational week, or roughly 18% of the initial cost. The computation time of the algorithm is evaluated by comparing with Simulated Annealing using a problem with the same size. VNTS has a lower average time and is expected to perform competitively when a standardized dataset is used for comparison. The solution quality of the algorithm is then compared with branch-and-bound method. VNTS is able to find one global optimal solution out of the six instances and overall, it performs better than branch-and-bound.